The Addition of Trichoderma sp. in Various Types of Organic Liquid Fertilizer to Increase NPK Nutrient Uptake and Soybean Production in Ultisol - Rapialdi, Rapialdi; Munir, Jamilah; Ernita, Milda (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2022)
Indonesia imports up to 70% of its domestic soybean needs from abroad. Therefore, it is necessary to increase soybean yields in Indonesia, among others, by providing Liquid Organic Fertilizer (LOF). The purpose of this study was to determine the effects of LOF enriched with Trichoderma sp. on the yield of Mutiara-1 soybean in Ultisol. The experiment was conducted on dry land with a pH of 4.66 (acidic) in Kuranji Village, Kuranji District, Padang. The experiment was arranged in a factorial completely randomized design consisting of two factors, including the dose of Trichoderma sp. and the type of LOF. The doses of Trichoderma sp. inoculants were 0, 1, and 2 kg for every 20 kg of fermented LOF main ingredients. The main ingredients of LOF used in this experiment were Chromolaena odorata, Tithonia diversifolia, and Trichoderma sp. Meanwhile, the type of LOF tested was according to the composition of the main ingredients, consisting of no LOF, Crocober, and Tithocroco. The data obtained were analyzed using ANOVA and continued with the LSD test at a 5% significance level. The results showed that the addition of 2 kg of Trichoderma sp. inoculants to Tithonia + C. odorata (Tithocroco) resulted in the highest dry seed production, reaching 3.17 tons ha-1 or an increase of 38.42% compared to those without LOF.